Comparison of the efficacy of intra-cervical foley’s catheter balloon with PGE2 gel in pre-induction cervical ripening - Perveena, Fareed; Neha, Mahajan; Farhana, Siraj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of this study was to compare the efficacy of intracervical Foleys catheter and intracervical PGE2 gel in preinduction cervical ripening. Methods: This randomized, prospective study was conducted in the Department of Obstetrics and Gynecology, Government Medical College Srinagar from Mar 2011- Mar 2013. Total 200 patients at term with a Bishop’s score <3 with various indications for induction were taken and randomly allocated to receive intracervical Foleys catheter (100pts) or PGE2 gel (100pts). After 6 hours post induction, bishop’s score was assessed. Various parameters noted were change in Bishop Score, induction delivery interval, mode of delivery fetal outcome and maternal complications. Statistical analysis was done using chi square test and t-test. Results: The groups were comparable with respect to maternal age, gestational age, indication of induction and preinduction bishop’s score. Both the groups showed significant change in the bishop’s score, 5.3+1.1 &5.1+1.1for Foleys catheter and PGE2 gel, respectively (p<0.001); however the difference between the two groups was not significant.14 cesarean sections (14%) were performed in group A and 20(20%) were performed in group B (NS). The induction to delivery interval was 15.34+5.3 h in group A and 14.2+5.2 h in group B (p= 0.29). Apgar score, birth weight, NICU admissions and maternal side effects showed no difference between the two groups. Conclusions: This study shows that both Foleys catheter and PGE2 gel are equally effective in pre induction cervical ripening.